Gelsolin Promotes Cancer Progression by Regulating Epithelial-Mesenchymal Transition in Hepatocellular Carcinoma and Correlates with a Poor Prognosis. (8th January 2020) - Zhang, Yixi; Luo, Xiaojing; Lin, Jianwei; Fu, Shunjun; Feng, Pei; Su, Hongjun; He, Xiangjun; Liang, Xue; Liu, Kunpeng; Deng, Wen
Abstract : Gelsolin (GSN), a cytoskeletal protein, is frequently overexpressed in different cancers and promotes cell motility. The biological function of GSN in hepatocellular carcinoma (HCC) and its mechanism remain unclear. The expression of GSN was assessed in a cohort of 188 HCC patients. The effects of GSN on the migration and invasion of tumour cells were examined. Then, the role of GSN in tumour growth in vivo was determined by using a cancer metastasis assay. The possible mechanism by which GSN promotes HCC progression was explored. As a result, GSN was overexpressed in HCC tissues. High GSN expression was significantly correlated with late Edmondson grade, encapsulation, and multiple tumours. Patients with high GSN expression had worse overall survival (OS) and disease-free survival (DFS) than those with low GSN expression. GSN expression was identified as an independent risk factor in both OS (hazard risk (HR) = 1.620, 95% confidence interval (CI) = 1.105–2.373, P < 0.001 ) and DFS (HR = 1.744, 95% CI = 1.205–2.523, P = 0.003 ). Moreover, GSN knockdown significantly inhibited the migration and invasion of HCC tumour cells, while GSN overexpression attenuated these effects by regulating epithelial-mesenchymal transition (EMT) In conclusion, GSN promotes cancer progression and is associated with a poor prognosis in HCC patients. GSN promotes HCC progression by regulating EMT.